(untitled) (Journal of Pharmaceutical Negative Results, 2024)
The present study is planned to investigate the effect of dandelion leaves water extract (DWE) on Schistosomiasis. Thirty-five adult male albino mice weighing 20-25 g were used and divided into two main groups, the main first group served as a normal control group without infection (n=7); the second main group was infected with S. mansoni (n=28). After 45 days post-infection the second main group was divided into four subgroups; the first subgroup infected with S. mansoni without treatment (IC) and served as positive control group, the second subgroup infected with S. mansoni then treated by praziquantel (PZQ), the third subgroup infected with S. mansoni then treated by DWE, and the fourth subgroup infected with S. mansoni then treated by DWE in combination with PZQ.The results indicated that administration of combined DWE+PZQ is more effective in all parameters than PZQ or DWE and exhibited highly significantly reduced parasitological parameters, the number and diameter of hepatic granulomas, and histopathological changes in the liver as compared to the untreated infected group. The results also showed that the administration of DWE+PZQ remarkably reduced AST and ALT activities and increment of serum albumin. These amelioration effects were observed in DWE+PZQ treated group, then PZQ‑treated group, followed by the group treated with DWE only. This study concluded that dandelion leaves water extract can be added as a potential treatment against schistosomiasis when combined with the anti-schistosomal drug praziquantel.